Validation of the Big Five model in rural developing economies: Evidence from Thailand and Vietnam - Dorothee Christine Bühler; Rasadhika Sharma; Wiebke Stein (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2020)
The Big Five model is widely used to measure and analyse personality traits in developed countries. However, there exist concerns regarding its validity in developing countries. We use a novel data set on personality traits from rural Thailand and Vietnam on around 4,000 individuals to test the universality of the model. We find that the measures demonstrate internal and external validity, and, that the analysis reveals a five factor structure similar to the Big Five model. In regard to stability of traits, we observe significant differences over time though the magnitude of differences is low. Also, gender and education influence the stability. We further test for acquiescence bias in our sample. While we find evidence for acquiescence bias, our results remain robust to its effect. We conclude that it is possible to employ the Big Five model to examine personality traits in rural Southeast Asia.
Keywords: D91; O1; R2; 330; Personality Traits; Big Five model; Southeast Asia; TVSEP